STUDI NUMERIK EVALUASI SUDUT DIVERGENSI TERHADAP KARAKTERISTIK ALIRAN FLUIDA DI DALAM SYMMETRIC FLAT-WALLED DIFFUSER - Rizka Nur Faila (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
Diffuser is one of the construction that is able to control the behavior of the fluid. Adverse pressure gradient (APG) causes boundary layer develops rapidly so that it causes separation and Cp becomes low. So that need to evaluating divergence angle of diffuser to delay the separation to get optimization Cp of diffuser. This study uses a numerical method with software Fluent 6.3.26 with k-ω turbulence model of shear stress transport (SST) for evaluate in a symmetric flat-walled diffuser with constant ratio in divergence angle (2θ1) = 8° and usedused the Reynolds number 12.9 x 104. Test section consisted of three parts, namely symmetric diffuser, upstream channels, and downstream channels. The symmetric diffuser has a length (L1) = 500 mm, the upstream channel length (L2) = 500 mm, and the downstream channel has a length (L3) = 1000 mm. The results of the study showed that there is no flow separation on the field at midspan vertical diffuser (2θ1) = 8 °. However, based on the velocity vector visualization, flow separation can be observed at midspan plane horizontal to diffuser (2θ1) = 8 ° indicated the occurrence of separation in the area after the inlet diffuser, ie at x / L1 = 1.4 and x / L1 = 1.6